PENGEMBANGAN LEMBAR KEGIATAN SISWA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL DENGAN PENDEKATAN OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS X SMA N 11 SEMARANG - Novia Irawati; Dwi Sulistyaningsih; Eko Andy Purnomo (Universitas Muhammadiyah Semarang, 2017)
This study aims to develop a Student Worksheet (LKS) with a valid open ended approach and its application in effective learning. This research is a development research using FOUR-D development model with define, design and develop stages. The sample of this research is class X IPA 6 (experiment) and class X IPA 1 (control). Data analysis techniques used are the test of completeness, influence test, average difference test and gain index calculation. The results showed that the developed LKS meet the criteria is very valid with the value of 85.2%. The ability to problem solving of KKM with an average value of 88.89%. The influence of activity and motivation on problem solving ability is 87,1% and there is difference of experiment class and control class. There is an increase in problem solving abilities by 0.7 with a high increase criteria. So it can be concluded that LKS with open ended approach on SPLTV material is valid, and effective. Keywords : Student Worksheet, Open Ended, Problem Solving Mathematics